The biomechanics of three different fracture fixation implants for distal femur repair in the presence of a tumor-like defect. (January 2013) - Ahmadi, Shahryar; Shah, Suraj; Wunder, Jay S; Schemitsch, Emil H; Ferguson, Peter C; Zdero, Rad
The femur is the most common long bone involved in metastatic disease. There is consensus about treating diaphyseal and epiphyseal metastatic lesions. However, the choice of device for optimal fixation for distal femur metaphyseal metastatic lesion remains unclear. This study compared the mechanical stiffness and strength of three different fixation methods. In 15 synthetic femurs, a spherical tumor-like defect was created in the lateral metaphyseal region, occupying 50% of the circumference of the bone. The defect was filled with bone cement and fixed with one of three methods: Group 1 (retrograde nail), Group 2 (lateral locking plate), and Group 3 (lateral nonlocking periarticular plate). Constructs were tested for mechanical stiffness and strength. There were no differences between groups for axial stiffness (Group 1, 1280 ± 112 N/mm; Group 2, 1422 ± 117 N/mm; and Group 3, 1403 ± 122 N/mm; p = 0.157) and offset torsional strength (Group 1, 1696 ± 628 N; Group 2, 1771 ± 290 N; and Group 3, 1599 ± 253 N; p = 0.816). In the coronal plane, Group 2 (296 ± 17 N/mm) had a higher stiffness than Group 1 (263 ± 17 N/mm; p = 0.018). In the sagittal plane, Group 1 (315 ± 9 N/mm) had a higher stiffness than Group 3 (285 ± 19 N/mm; p = 0.028). For offset torsional stiffness, Group 1 (256 ± 23 N/mm) had a higher value than Group 3 (218 ± 16 N/mm; p = 0.038). Group 1 had equivalent performance to both plating groups in two test modes, and it was superior to Group 3 in two other test modes. Since a retrograde nail (i.e. Group 1) would require less soft-tissue stripping in a clinical context, it may be the optimal choice for tumor-like defects in the distal femur.